The haemocytes of the salp Thalia democratica (Tunicata, Thaliacea): an ultrastructural and histochemical study in the oozoid. (8th May 2013) - Cima, Francesca; Caicci, Federico; Sordino, Paolo
Abstract In comparative immunology and evolution of the chordate immune system, tunicates hold an important phylogenetic position as sister group of vertebrates. However, knowledge of the tunicate immune system is limited to the class Ascidiacea, in which some species are now considered model organisms. In the class Thaliacea, represented by fragile pelagic species, the few studies on their haemocytes go back to several decades ago and do not consider comparative aspects with ascidian haemocytes. In this study, we identified various haemocyte types and their distribution in the common salp Thalia democratica by comparative observations under light and electron microscopy and by histochemical, histoenzymatic and immunohistochemical techniques. By comparing specialisations with those of ascidian haemocytes, we detected an undifferentiated cell type (lymphocyte‐like cell) and three categories with four cell types, that is, (i) phagocytic line (hyaline amoebocyte and amoebocyte with large vacuoles), (ii) mast cell‐like line (granular cell) and (iii) storage cells (nephrocyte). Both phagocytes and granular cells appear to migrate in the tunic. Phagocytes adhere to the tunic which internally covers the oral siphon, where they probably function as sentinel cells of the pharynx. Results show the variety of haemolymph cells in the salp similar to phlebobranch ascidians.